2013
DOI: 10.1890/12-0782.1
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem‐level consequences of symbiont partnerships in an N‐fixing shrub from interior Alaskan floodplains

Abstract: In long-lived N-fixing plants, environmental conditions affecting plant growth and N demand vary at multiple temporal and spatial scales, and symbiont assemblages on a given host and patterns of allocation to nodule activities have been shown to vary according to environmental factors, suggesting that hosts may alter partner choice and manipulate symbiont assemblages based on shifting plant needs. This study assessed economic trade-offs among N-fixing symbionts of thin-leaf alder (Alnus tenuifolia) by examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(56 citation statements)
references
References 114 publications
3
53
0
Order By: Relevance
“…To quantify field rates of N 2 ‐fixation for each sample, we used an isotopic enrichment approach modified from Ruess et al . (). Each sample was placed in a 60 ml translucent polycarbonate syringe that was depressed to contain 10 ml of air.…”
Section: Methodsmentioning
confidence: 97%
“…To quantify field rates of N 2 ‐fixation for each sample, we used an isotopic enrichment approach modified from Ruess et al . (). Each sample was placed in a 60 ml translucent polycarbonate syringe that was depressed to contain 10 ml of air.…”
Section: Methodsmentioning
confidence: 97%
“…or Dryas sp.) often dominates floodplains, increasing carbon and nitrogen availability simultaneously, as water moves downstream (Ruess et al, 2013;Taylor, 2013;Malone et al, 2018). Furthermore, headwater aquatic primary production (algae) is often phosphorus limited, resulting in rapid nitrification of what little ammonium makes it to the stream channel, though nitrogen demand increases as rivers meet the sea McClelland et al, 2012).…”
Section: Riparian Corridors Function As Kidneys Of River Systemsmentioning
confidence: 99%
“…Ruess et al. () estimated nodule respiration, N fixation, and Frankia strain identity in a field survey of Alnus tenuifolia and found that Frankia strains vary in terms of both N fixation and respiratory cost. Some inocula in our study seem to be low quality in terms of N fixation ability (based on C:N and δ 15 N, relative to other inocula), resulting in N‐limited plants independent of C availability, while others appeared to fix more N and thus allow hosts to respond positively to increased C availability, though for some (262) only in ambient light, potentially because of substantial C costs.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizobium strains are well known to vary in partner quality, which is most often measured as relative plant growth and fitness (reviewed by Denison, 2000;Simms and Taylor, 2002;Heath and Stinchcombe, 2014;Sachs et al, 2018). These growth and fitness benefits to the plant depend on both the benefits and costs of symbiosis, i.e., the benefits of fixed N received minus the C costs including nodule formation, nodule respiration, and production of the bacterial storage compound poly-3-hydroxybutyrate (PHB) (Tjepkema and Winship, 1980;Minchin and Witty, 2005;Ratcliff et al, 2008;Ruess et al, 2013). Plant nutrient status and light interactively determine plant growth (reviewed by Elser et al, 2010); therefore, genetic variation in N-fixing rhizobium symbionts may interact with light availability to influence the outcome of mutualism for plant hosts.…”
mentioning
confidence: 99%